Determinants of Dividend Payments of Non-financial Listed Companies in Hồ Chí Minh Stock Exchange - Nguyễn, Kim Thu (Đại học Quốc gia Hà Nội, 2014)
This research aims to examine the determinants of dividend payments of non-financial listed companies in the HồChí Minh Stock Exchange (HOSE) in the period 2007 to 2012. Using the Pooled Ordinary Least Square and the Fixed effect model (FEM) for panel data, the authors found that in HOSE, the profitability of firms is statistically significant and negatively related to payout ratio (DPR). In other words, companies tend to plow back more earnings when profitability increases. Moreover, leverage has a positive and statistically significant relationship with DPR. There are no statistically significant differences in DPRs among accommodation services, mineral ore exploitation, investment consulting services and related services, supporting services, scientific and technical services and the other services industry. Meanwhile, DPRs in the remaining industries are statistically lower than those of the above-mentioned industries.